High Curie temperature and perpendicular magnetic anisotropy in homoepitaxial InMnAs films. (17th June 2015) - Yuan, Y; Wang, Y; Gao, K; Khalid, M; Wu, C; Zhang, W; Munnik, F; Weschke, E; Baehtz, C; Skorupa, W; Helm, M; Zhou, S
Abstract We have prepared the dilute magnetic semiconductor (DMS) InMnAs with different Mn concentrations by ion implantation and pulsed laser melting. The Curie temperature of the In1−xMnxAs epilayer depends on the Mn concentration x, reaching 82 K for x = 0.105. The substitution of Mn ions at the indium sites induces a compressive strain perpendicular to the InMnAs layer and a tensile strain along the in-plane direction. This gives rise to a large perpendicular magnetic anisotropy, which is often needed for the demonstration of the electrical control of magnetization and for spin-transfer-torque induced magnetization reversal.